Investigation of the Mn3-ΔGa/MgO interface for magnetic tunneling junctions - Violbarbosa, C. E.; Ouardi, Siham; Kubota, Takahide; Mizukami, Shigemi; Fecher, G. H.; Miyazaki, T.; Kozina, X.; Ikenaga, E.; Felser, Claudia (Journal of Applied Physics, 2014)
The Mn3Ga Heusler compound and related alloys are the most promising materials for the realization of spin-transfer-torque magnetoresistive memories. Mn-Ga films exhibits perpendicular magnetic anisotropy and high spin polarization and can be used to improve the performance of MgO-based magneto tunneling junctions. The interface between Mn-Ga and MgO films were chemically characterized by hard x-ray photoelectron spectroscopy. The experiment indicated the formation of Ga-O bonds at the interface and evidenced changes in the local environment of Mn atoms in the proximity of the MgO film. We show that the deposition of few monoatomic layers of Mg on top of Mn-Ga film, before the MgO deposition, strongly suppresses the oxidation of gallium. © 2014 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20